A multi-phase oscillated variable neighbourhood search algorithm fora real-world open vehicle routing problem - Sevkli, Aise Zulal; Guler, Bekir (ELSEVIER, 2017)
The aim of this study is to solve the newspaper delivery optimization problem for a media delivery company in Turkey by reducing the total cost of carriers. The problem is modelled as an open vehicle routing problem (OVRP), which is a variant of the vehicle routing problem. A variable neighbourhood search-based algorithm is proposed to solve a real-world OVRP. The proposed algorithm is tested with varieties of small and large-scale benchmark suites and a very large-scale real-world problem instance. The results of the proposed algorithm provide either the best known solution or a competitive solution for each of the benchmark instances. The algorithm also improves the real-world companys solutions by more than 10%. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Metaheuristic; Open vehicle routing problem; Variable neighbourhood search; Deterministic oscillated perturbation; Computer Science